The Culture is Prevention Project: measuring cultural connectedness and providing evidence that culture is a social determinant of health for Native Americans - Paul Masotti; John Dennem; Karina Bañuelos; Cheyenne Seneca; Gloryanna Valerio-Leonce; Christina Tlatilpa Inong; Janet King (BMC, 2023)
Abstract Background It is important for non-Native persons to understand that the meaning of culture to Native American/Indigenous Peoples is not about esteem, taste or music but rather is described as a cognitive map on how to be. Native American/Indigenous culture can be thought of as all the things and ways in which Native/Indigenous people understand who they are, where they come from and how they are to interact with others. Hundreds of years across many generations have taught that culture-based activities and interventions improve Native/Indigenous health and wellbeing. We explore if increased Native American culture/cultural connectedness is associated with better mental health/well-being and physical health. Methods We analyzed data from a two-phased study (N = 259 and N = 102) of 361 urban Native Americans in California (2018-2021). The 29 items validated Cultural Connectedness Scale-California (CCS-CA) measured Native culture/cultural connectedness. Mental health/well-being and physical health were assessed using the: modified Herth Hope Index (mHHI), Satisfaction with Life (SWL), Center for Epidemiologic Studies Depression Scale-Revised (CESD-R-10), Substance Abuse (CAGE-AID), and Health Related Quality of Life (HRQOL). We conducted Pearson correlations and stepwise regression analyses with CCS-CA as the independent (predictor) variable to explore our main research questions: 1) Is increased Native American/Indigenous culture associated with: 1) better mental health/well-being; and 2) better physical health? Results Increased Native/Indigenous culture (CCS-CA scores) is significantly associated with better mental health/well-being (mHHI, p < .001) and satisfaction with life (SWL, p < .001) predicts good physical health days (HRQOL, p < .001). Increased connection to Native American/Indigenous culture (CCS-CA scores) is significantly associated with decreased risk for depression (CESD-R-10, p < .0) and substance abuse and (CAGE-AID, p < .07). Significant results for culture as protective against risk for substance abuse (CAGE-AID) was most likely affected (p value approaching significance) due to an error in language on the measure (i.e., created double negative). Conclusions Native American/Indigenous culture is a predictor of improved outcomes for mental health/well-being and physical healthy days. Native culture is an important social determinant of health. We add to the evidence that Native/Indigenous culture (i.e., cultural connectedness) be considered an important intervention objective and health-related outcome measure.